2020
DOI: 10.1029/2020jd033153
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of Conceptual Schemas of Surface Synoptic Meteorological Situations Affecting Fine Particulate Pollution Across Eastern China in the Winter

Abstract: In the present study, the characteristics of weather conditions and local meteorological variables over the Beijing‐Tianjin‐Hebei (BTH) and the Yangtze River Delta (YRD) regions in the winter are analyzed using the principal component analysis (PCA) method and daily PM2.5 accumulation rate. Typical synoptic weather patterns over China in the winter can be classified into four types. During the Type 1 synoptic weather pattern, China is under the influence of the Siberian High, and northerly winds prevail; this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 57 publications
0
18
0
Order By: Relevance
“…Meteorological effects are different in summer and winter [93]. Different synoptic situations in the winter result in different transport pathways and pollution episodes in the BTH and YRD [12].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Meteorological effects are different in summer and winter [93]. Different synoptic situations in the winter result in different transport pathways and pollution episodes in the BTH and YRD [12].…”
Section: Discussionmentioning
confidence: 99%
“…The AOD over China shows strong spatial variability due to a variety of influences, as discussed in the Introduction section. Several studies were made to explain these variations in terms of transport pathways using meteorological information [12] and air mass trajectory analysis [44]. Wang et al [44] used sun photometer data together with ground-based data from Nanjing during episodes with heavy pollution, in the summer and in the winter.…”
Section: Spatiotemporal Variation Of Aerosols Over China and Application In Air Quality Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it is reasonable to observe the TRT haze events from the NCP to YRD in winter because of cold fronts (He et al., 2018; Kang et al., 2019). Although a few studies have observed some TRT haze events from the NCP to YRD during winter, they only analyzed the impact of weather system on TRT by weather patterns (He et al., 2018; Hou et al., 2020; J. Li et al., 2019; Shu et al., 2017) or variations of components and geographical contribution of PM 2.5 in the YRD during TRT by bulk analysis (Li, Wang, et al., 2019; Ming et al., 2017), radiosonde observation (Zhong et al., 2019), lidar measurement (T. Sun et al., 2018), and model simulation (X. Huang et al., 2020; Kang et al., 2019; Li, Huang, et al., 2012; Ming et al., 2017). For example, He et al.…”
Section: Introductionmentioning
confidence: 99%